Effects of the New Public Management (NPM) and Austerity in European Public and Academic Libraries. Issue 3 (3rd April 2019) - Düren, Petra; Goldstein, Stéphane; Landøy, Ane; Repanovici, Angela; Saarti, Jarmo
Abstract: The changing information landscape calls for a new leadership, new competences, and new approaches to library services. In today's information age, information literate citizens must be able to assess the reliability of information, making information literacy instruction an important task for libraries. In this paper, five researchers present data from interviews they carried out with library leaders from Germany, Romania, Finland, UK, and Norway. The experiences of the library leaders were different, reflecting varying levels of economic austerity, and how closely each country adheres to New Public Management (NPM)-theory and practice. However, they also show how NPM and reduced budgets can lead to a greater and better cooperation.